Orientaciones didácticas para el desarrollo de la lectoescritura, en los niños y niñas de segundo grado de educación básica de la unidad educativa Óscar Efren Reyes, de la comunidad Guantul grande, parroquia Flores, Riobamba, Chimborazo, periodo 2014-2015 - Puma Lema, José Raúl (2016)
It arises, in order to identify the importance of the teaching guidelines for the development of literacy in children. This research is important because it prioritizes problems that may lead avoid work with the teaching guidance on literacy it is a cognitive process that requires some perceptual maturity, especially in the visual, hearing and motricity areas, therefore this research is focused on the subject of teaching guidelines aspect with a high degree of attention, starting from the idea that it is not that the child learns the letters and their sounds, words, and their meanings, but to establish a psychomotor skills relationship to the act of producing language to communicate effectively with the natural and the social. The study was inductive type since it split from private analysis later reach general statements and documentary problems were studied with the purpose to broaden and deepen the knowledge of their nature, to analyze the results observation sheets were made, then some findings diagnosis was identified and showed that the highest percentage of children have difficulty in laterality. In a conclusion of this paper, there is difficulty in the level of literacy development also applying different strategies in reading helps students to establish cause and effect, and to understand what they read. Recommending that the teacher's role is to mediate, guide, assist and arouse interest in the process in which students develop their knowledge, skills, abilities and attitudes.